Mariss Jansons conducts Mahler, Copland, Bartók, Padding -- With Thomas Hampson Mariss Jansons's farewell concert with the Royal Concertgebouw Orchestra - Mahler, Gustav 1860-1911; Mahler, Gustav 1860-1911; Mahler, Gustav 1860-1911; Mahler, Gustav 1860-1911; Padding, Martijn; Niles, John Jacob 1892-1980; Copland, Aaron 1900-1990; Copland, Aaron 1900-1990; Copland, Aaron 1900-1990; Copland, Aaron 1900-1990; Bartók, Béla 1881-1945 (Royal Concertgebouw, 2015)
For one final time, the great Mariss Jansons descended the red carpeted stairs of the storied Concertgebouw: it would be his final turn as the Royal Concertgebouw Orchestra's principal conductor after over a decade in that capacity, and after many decades of glorious music. Jansons first conducted the RCO in 1988, and his immediate rapport with the ensemble only grew over the years, culminating in his appointment as principal conductor in 2004. This momentous program was part of the AAA Festival, centered around a theme of composers inspired by folk music. Celebrated baritone Thomas Hampson interprets works from two very different folk traditions: Mahler's Des Knaben Wunderhorn, a collection of folk songs and popular legends from the heart of Germany; and a selection from the Old American Songs by Aaron Copland, one of the greatest American composers, who broke free from European influences and created a uniquely American musical idiom. Jansons also conducts Ick seg adieu (I bid you adieu) by Dutch composer Martijn Padding, an apt work commissioned just for this concert, as well as Bartók's spirited Concerto for Orchestra. Having fled Hungary during wartime and already afflicted with leukemia in his adopted America, Bartók created a work that would become one of his best-loved, symbolic of "the passage of austerity and funereal dirges ... into an affirmation of life." The perfect choice, indeed, to mark the end of Jansons's spectacular career
Keywords: Songs (Medium voice) with orchestra; Song cycles; Folk songs, English; Concertos (Orchestra); Song cycles -- Excerpts; Songs; Folk songs; Concertos; Concert films; Internet videos